Meet the Fockers - Roach, Jay.; De Niro, Robert; Stiller, Ben, 1965-; Hoffman, Dustin, 1937-; Streisand, Barbra; Danner, Blythe; Polo, Teri, 1969-; Schwartzman, John.; Newman, Randy; Glienna, Greg.; Clarke, Mary Ruth.; Universal Pictures (Firm); et al. (Universal City, CA : Universal, 2005)
When Pam and Greg get their parents together it turns into one disaster after another. The hippie Fockers are the direct opposite of the uptight Byrneses. With one pitfall after the next, the film takes awkward in-law experiences to new heights.
English track: Dolby digital 5.1.
Spanish track: Dolby digital 5.1.
French track: Dolby digital 5.1.
Originally released as a motion picture in 2004.
Based on characters created by Greg Glienna and Mary Ruth Clarke.
Title from disc.
Keywords: Parents-in-law -- Drama; Feature films; Comedy films